Electron emission in collisions between dressed Alq+ ions with He targets - Monti, Juan Manuel (2013)
Experimental and theoretical results are presented for electron emission in collisions between dressed Alq+ ions and atomic He targets. The experimental data are compared with a four-body CTMC model and two distorted wave models, namely the CDW and CDW-EIS. The contribution to total electron emission spectra from the ionisation of each collision center and as well as the simultaneous ionisation can be assessed separately.